Establishment of immortalized rabbit bone marrow mesenchymal stem cells and a preliminary study of their osteogenic differentiation capability - Yao Zhang; Chang Xu; Yun Huang; Dongmei Tan; Wenping Luo; Yan Zhang; Yi Tan (Animal Models and Experimental Medicine)
Abstract Background A stable and standardized source of mesenchymal stem cells is a prerequisite for bone repair tissue engineering research and application. We aimed to establish a stable cell line of bone marrow mesenchymal stem cells from New Zealand rabbits and explore their osteogenic differentiation capacity. Methods Primary rabbit bone marrow mesenchymal stem cells (RBMSCs) were isolated and immortalized via retroviral expression of SV40 Large T antigen (LTA). To assess the osteogenic differentiation capacity of the cells in vitro, we studied the alkaline phosphatase (ALP) expression level and calcium deposition in bone morphogenetic protein 9 (BMP9)‐induced immortalized cells using ALP staining and quantification, as well as alizarin red staining. Ectopic bone formation by the cells was assessed using micro‐computed tomography (μCT) and histological examination. Results The immortalized cell line we established using SV40 LTA, which we termed iRBMSCs, was non‐tumorigenic and maintained long‐term proliferative activity. We further discovered that BMP9 (MOI = 30) effectively induced the osteogenic differentiation capacity of iRBMSCs in vitro, and there was a synergy with GelMA hydrogel in inducing osteogenic differentiation of the iRBMSCs in vivo. Conclusion We confirmed that iRBMSCs are promising as a stable cell line source for bone defect repair engineering.